Impact of probe-induced abdominal compression on two-dimensional shear wave elastography measurement of split liver transplants in children - Groth, Michael; Fischer, Lutz; Herden, Uta; Brinkert, Florian; Beime, Jan; Deindl, Philipp; Adam, Gerhard; Herrmann, Jochen (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To evaluate the effect of probe-induced abdominal compression of split liver transplants (SLT) in children on 2D-shear wave elastography (SWE) values.Materials and Methods Data from 11 children (4.7 ± 4.8 years) who had undergone SLT and SWE were evaluated retrospectively. Elastograms were obtained with probes placed in an epigastric, midline position on the abdominal wall, with no and slight compression, using convex and linear transducers. For each identically positioned probe and condition, 12 serial elastograms were obtained and the SLT diameter was measured. Liver stiffness and degree of SLT compression were compared.Results Slight probe pressure resulted in SLT compression, with a shorter distance between the cutis and the posterior margin of the liver transplant than in the measurement with no pressure (curved array, 5.0 ± 1.1 vs. 5.9 ± 1.3 cm, mean compression 15 %± 8 %; linear array, 4.7 ± 0.9 vs. 5.3 ± 1.0 cm, mean compression 12 %± 8 %; both p < 0.0001). The median liver stiffness was significantly greater with slight pressure than with no pressure (curved transducer, 13.38 ± 3.0 vs. 7.02 ± 1.7 kPa, p < 0.0001; linear transducer, 18.53 ± 7.1 vs. 9.03 ± 1.5 kPa, p = 0.0003).Conclusion Slight abdominal compression can significantly increase SWE values in children with left-lateral SLT. To obtain meaningful results and reduce operator dependency in free-hand examinations, probe pressure must be controlled carefully.Key points: Citation Format
Keywords: elasticity imaging techniques; ultrasonography; liver transplantation; child; pressure